2020
DOI: 10.1080/10942912.2020.1815767
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive insight into the metabolic landscape of fruit pulp, peel, and seed in two longan (Dimocarpus longanLour.) varieties

Abstract: Longan is an ancient and popular plant with highly nutritious fruit. The pulp is the main part of the fruit which is consumed. However, the potentials of other longan fruit parts such as the peel and the seed as reservoirs of important bioactive components have not yet fully been explored. This study aimed at exploring the diversity of primary and secondary metabolites in two commercial longan varieties, i.e., Shixia and Chuliang, concerning fruit, pulp, peel, and seed based on a widely targeted metabolomics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 63 publications
0
6
0
1
Order By: Relevance
“…KEGG (Kyoto Encyclopedia of Gene and Genomes) enrichment of expanded and contracted gene families ( P < 0.05 ) showed that the 312 expanded gene families were significantly enriched with “phenylpropanoid biosynthesis”, “phenylalanine metabolism”, “anthocyanin”, “sesquiterpenoid and triterpenoid biosynthesis”, “monoterpenoid biosynthesis” (Figure 3D). Longan is rich in flavonoids and polyphenols, with anti-cancer, anti-oxidant properties in leaf, flower, fruits, and seeds 24, 31, 32, 33 , which are derived primarily through phenylpropanoid pathways. The branches of phenylpropanoid metabolism produce end products such as flavonoids, hydrox-ycinnamic acid esters, hydroxycinnamic acid amides (HCAAs), and the precursors of lignin, lignans, and tannins 34 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…KEGG (Kyoto Encyclopedia of Gene and Genomes) enrichment of expanded and contracted gene families ( P < 0.05 ) showed that the 312 expanded gene families were significantly enriched with “phenylpropanoid biosynthesis”, “phenylalanine metabolism”, “anthocyanin”, “sesquiterpenoid and triterpenoid biosynthesis”, “monoterpenoid biosynthesis” (Figure 3D). Longan is rich in flavonoids and polyphenols, with anti-cancer, anti-oxidant properties in leaf, flower, fruits, and seeds 24, 31, 32, 33 , which are derived primarily through phenylpropanoid pathways. The branches of phenylpropanoid metabolism produce end products such as flavonoids, hydrox-ycinnamic acid esters, hydroxycinnamic acid amides (HCAAs), and the precursors of lignin, lignans, and tannins 34 .…”
Section: Resultsmentioning
confidence: 99%
“…Longan leaf, flower, fruits, and seeds 9,10 are rich in polyphenols with anti-cancer, anti-oxidant properties, biosynthesized primarily through the shikimic acid, flavonoid and phenylpropanoid pathways. Phenylpropanoid pathway is one of the most extensively investigated specialized metabolic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al [ 35 ] identified a total of 27 FAAs in dried longan pulp. Based on a widely targeted metabolomics approach, Wang et al [ 6 ] had identified 706 metabolites (including ~98 FAAs and their derivatives) from fruit pulp, peel, and seed in two longan varieties i.e., ‘Shixia’ and ‘Chuliang’. Besides, Huang et al [ 21 ] determined 18 kinds of FAAs in ‘Lidongben’ during the fruit development phase and tree hanging phase (3 stages each), the total content of the 18 FAAs ranged from 7.6 to 9.1 g∙kg −1 , but the selected variety was a non-aromatic genotype.…”
Section: Discussionmentioning
confidence: 99%
“…is an economically important crop in tropical and subtropical regions of Southeast Asia i.e., China, Thailand, Vietnam, etc. Longan possesses numerous nutritional and functional components, including polysaccharides [ 1 ], amino acids [ 2 , 3 ], polyphenols and alkaloids [ 4 , 5 ], flavonoids, lipids [ 6 ], organic acids, vitamin C, minerals [ 7 , 8 ], and volatile compounds [ 9 ]. Amino acids exist in both bound and free forms in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies emphasized valorization of plant biowaste by utilizing a broad spectrum of bioactive compounds present in plant parts generally considered biowaste. Deng et al (2020) and Wang et al (2020a), in their studies on banana pseudo-stem and longan fruit parts (skin and seed), respectively, demonstrated the potential valorization of biowaste by exploiting the metabolome and identified several compounds with nutraceutical properties. Hence, investigating the metabolome composition of black tiger fruit parts could open a new avenue towards a better valorization of the fruit and the development of the industry.…”
Section: Introductionmentioning
confidence: 99%